Kajian Evaluasi Perlintasan Sebidang di Jalur Perlintasan Langsung (JPL) di Kota Semarang - Budiharjo, Anton; Habibah, Fistirika; Tohom, Frans (Department of Civil Engineering, Diponegoro University, 2024)
As a mass transportation system infrastructure, level crossings impact road users, including skidding, roaddamage, and accidents. Based on data from KAI DAOP 4 Semarang, there were 12 accidents at level crossingsin 2023, while in 2024, the number increased to 26, indicating a rise in accident rates. One accident that wentviral on social media occurred in Semarang in 2023, involving a low-bed trailer that got stuck at a levelcrossing. The objective of this study is to analyze and evaluate level crossings, assess their compliance withregulations, and provide recommendations for improvements. This research employs the triangulation method,utilizing data obtained from geometric surveys and an inventory of crossing equipment. The study focuses onlevel-crossing locations JPL 6 Madukoro and JPL 5 Kaligawe in Semarang City. The findings indicate that theexisting conditions do not fully comply with regulatory requirements in terms of facilities and geometricspecifications. Specifically, the Madukoro crossing is constructed at a higher elevation than the surroundingtopography, creating a hump with a height of 86 cm above the road surface and a grade of 12.8%. Thiscondition increases the risk of long vehicles, such as low-bed trailers, getting stuck, potentially leading tosevere accidents. Therefore, it is recommended that regulations concerning level crossings be reviewed andrevised.